2013
DOI: 10.1177/159101991301900106
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Procedural Morbidity and Mortality Associated with Stent-Assisted Coiling for Intracranial Aneurysms

Abstract: Despite experience and technological improvements, stent-assisted coiling for intracranial aneurysms still has inherent risks. We evaluated peri-procedural morbidity and mortality associated with stent-assisted coiling for intracranial aneurysms. Patients with cerebral aneurysms that were broad-based (>4 mm) or had unfavorable dome/neck ratios (<1.5) were enrolled in this study between February and November 2011 at our center. Aneurysms were treated with the self-expanding neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…If we restricted the analysis to unruptured or nonacutely ruptured aneurysms, the rates of morbidity and mortality varied between 3.8%-8.3% and 0%-3.9%, respectively. [28][29][30][31][32][33][34] The data presented in our study show a safety profile comparable with that of stentassisted coil embolization.…”
supporting
confidence: 63%
“…If we restricted the analysis to unruptured or nonacutely ruptured aneurysms, the rates of morbidity and mortality varied between 3.8%-8.3% and 0%-3.9%, respectively. [28][29][30][31][32][33][34] The data presented in our study show a safety profile comparable with that of stentassisted coil embolization.…”
supporting
confidence: 63%
“…Although the long-term durability of SAE has been suggested previously, 6,11,16 there have been fewer reports on the complications associated with this intervention. 4,13,28,34 In the present study, the overall complication rate was 11.7%, whereas the major, permanent morbidity/mortality rate was 3.3%. In a recent publication regarding long-term follow-up for a similarly sized series of patients who underwent SAE, Jahshan et al 16 found a permanent event-related morbidity rate of 4.3% in 489 cases.…”
Section: Discussionmentioning
confidence: 87%
“…the use of an adjunctive device, (2) thromboembolic complication due to insufficient premedication, and (3) patient burden of prolonged general anesthesia. 1)10)11) 15) In summary, in cases with a K-ratio <1.3, we found that adjunctive devices were used heavily when treating unruptured aneurysms with sufficient premedication.…”
mentioning
confidence: 78%